2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00137
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Depth Completion with Boundary Consistency and Self-Attention

Abstract: Depth estimation features are helpful for 3D recognition. Commodity-grade depth cameras are able to capture depth and color image in real-time. However, glossy, transparent or distant surface cannot be scanned properly by the sensor. As a result, enhancement and restoration from sensing depth is an important task. Depth completion aims at filling the holes that sensors fail to detect, which is still a complex task for machine to learn. Traditional hand-tuned methods have reached their limits, while neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 39 publications
0
79
0
Order By: Relevance
“…The RMSE and MAE were calculated in meters. The results showed that the proposed method with the Guidance branch based on UNet was slightly worse than the method proposed in [30]. However, it is noticeable that it had a higher percentage of inliers, as shown by the δt and SSIM values.…”
Section: Comparison Of Depth Completion Methods On the Matterport3d Datasetmentioning
confidence: 87%
See 4 more Smart Citations
“…The RMSE and MAE were calculated in meters. The results showed that the proposed method with the Guidance branch based on UNet was slightly worse than the method proposed in [30]. However, it is noticeable that it had a higher percentage of inliers, as shown by the δt and SSIM values.…”
Section: Comparison Of Depth Completion Methods On the Matterport3d Datasetmentioning
confidence: 87%
“…The best result is shown in bold. The RMSE of the FCN is from [21], that for the MRF is from [57], and that for the bilateral filter was given in [30]. For the RMSE and MAE, lower is better.…”
Section: Comparison Of Depth Completion Methods On the Matterport3d Datasetmentioning
confidence: 99%
See 3 more Smart Citations